Innovation outlook : offshore wind (International Renewable Energy Agency, 2016)
IRENA's Renewable Energy Innovation Outlook series analyses the emerging developments making renewable energy technologies (RETs) increasingly competitive in the world's energy markets and systems. Renewable mini-grids, offshore wind technologies, advanced liquid biofuels, and ocean energy technologies open the series, with other key technologies, infrastructure, applications and products to follow. The series as a whole examines ways to further enhance the competiveness of RETs. Each Innovation Outlook identifies technology-, industry- and policy-related challenges to be overcome and assesses the potential breakthroughs and research needed to scale-up the deployment of renewable-based solutions. This book shows how policy and technological breakthroughs can move the development of this key renewable energy technology forward. Offshore wind technology opens up sites with high wind resources. Sites can be built quickly, at gigawatt (GW) scale, close to key markets, making offshore wind an important addition to the technology portfolio to cost-effectively decarbonise the energy sector. Offshore wind capacity looks set to reach 100 GW by 2030 as innovation continues and the industry matures. It could increase considerably faster with more ambitious policies.